2011
DOI: 10.5194/angeo-29-181-2011
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric vorticity at high geomagnetic latitudes from CHAMP data and its IMF dependence

Abstract: Abstract. Neutral thermospheric wind pattern at high latitudes obtained from cross-track acceleration measurements of the CHAMP satellite above both polar regions are used to deduce statistical neutral wind vorticity distributions and were analyzed in their dependence on the Interplanetary Magnetic Field (IMF). The average pattern confirms the large duskside anticyclonic vortex seen in the average wind pattern and reveals a cyclonic vorticity on the dawnside, which is almost equal in magnitude to the duskside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 32 publications
5
69
0
Order By: Relevance
“…Such a pattern corresponds to ByIMF and BzIMF (sector 5) neutral wind circulations at high latitudes [cf. Förster et al , ].…”
Section: Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a pattern corresponds to ByIMF and BzIMF (sector 5) neutral wind circulations at high latitudes [cf. Förster et al , ].…”
Section: Model Resultsmentioning
confidence: 99%
“…The guiding idea of this study is to analyze statistically the model simulation results of neutral thermospheric wind and ionospheric plasma drift at high latitudes in the same manner as it was done with the observational data of the CHAMP accelerometer wind estimations [ Förster et al , ; Förster et al , ] and the Cluster/Electron Drift Instrument (EDI) drift measurements [ Haaland et al , ; Förster et al , ]. We compare the two different model simulations with each other and consider their principal behavior in the context of observational findings.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, it has been found that the amplitude and direction of the IMF B y component, which plays an important role in the development of ionospheric storms, may be one of the factors that impacts the hemispheric asymmetry [Crowley et al, 2010;Förster et al, 2011;Mannucci et al, 2014;Astafyeva et al, 2015]. In recent years, it has been found that the amplitude and direction of the IMF B y component, which plays an important role in the development of ionospheric storms, may be one of the factors that impacts the hemispheric asymmetry [Crowley et al, 2010;Förster et al, 2011;Mannucci et al, 2014;Astafyeva et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Ion drag at F region altitudes can accelerate the neutral wind toward the ion convection velocity. Both plasma drift and neutral wind are found to respond in the similar way to the interplanetary magnetic field (IMF) [e.g., Thayer et al , 1987; Emmert et al , 2006; Förster et al , 2011]. Emmert et al [2006] found that the response of high latitude wind to plasma convection is broadly maximized at a time lag of 1 hour at around 250 km altitude during quiet time.…”
Section: Introductionmentioning
confidence: 99%